2014
DOI: 10.1111/nyas.12555
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐of‐society monitoring framework for sugar, salt, and fat consumption and noncommunicable diseases in India

Abstract: India has experienced a rising prevalence of cardiometabolic risk factors in the past 15 years: the prevalence of diabetes has increased from 5.9% to 9.1%, hypertension from 17.2% to 29.2%, and obesity from 4% to 15%. The increase is among all socioeconomic groups and in urban and rural populations, though the quantum of change varies. A concomitant increase in per capita consumption of sugar from 22 to 55.3 g/day and total fat from 21.2 to 54 g/day was observed, with significant differences between states of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 31 publications
0
24
0
1
Order By: Relevance
“…This was consistent with the ecological study of the UK and other previous studies. [24][25][26] Also, a Swiss study found a positive association between obesity and salt intake. 27 This was also consistent with the policy and action on nutrition and health promotion in many countries.…”
Section: Discussionmentioning
confidence: 99%
“…This was consistent with the ecological study of the UK and other previous studies. [24][25][26] Also, a Swiss study found a positive association between obesity and salt intake. 27 This was also consistent with the policy and action on nutrition and health promotion in many countries.…”
Section: Discussionmentioning
confidence: 99%
“…Per capita fat and oil consumption has also increased during the last 40 years. 42,45 Per capita consumption of sugar has increased from 22 to 55 g per day and total fat from 21 to 54 g per day in the last 15 years, more in rural populations. 43 National Nutrition Monitoring Bureau has also reported that fat consumption in India has increased significantly.…”
Section: Hypertension Risk Factors and Urban-rural Convergencementioning
confidence: 98%
“…This has led to 60% increase in number of towns in the last 20 years. 9 This process is known as 'diffuse urbanization' and has led to changes in hypertension risk behaviors and risk factors-sedentariness, stress, increased salt, sugar and fat intake and obesity, 1,42 and has led to more rapid increase in hypertension in rural populations. There is epidemiological evidence that population demographic changes in India have added to environmental risk factors for hypertension.…”
Section: Hypertension Risk Factors and Urban-rural Convergencementioning
confidence: 99%
“…Fat intake increased by 7% in India from 1980 to (FAO, 2004. Accordingly, the diet has shifted from one that is high in monounsaturated fat, present in olives, nuts and seeds, to a diet that is high in saturated and trans fats, present in fatty meats, dairy products, vegetable oil, snacks food and fast food (Arora et al, 2014). Currently, India imports about 18 million metric tons of vegetable oil yearly (Directorate General of Commercial Intelligence and Statistics -India, 2016).…”
Section: Trends In Dietary Consumptionmentioning
confidence: 99%